Peran Diplomasi Indonesia dalam Memobilisasi Sumber Daya Filantropi Global untuk Agenda Vaksinasi TBC Nasional - Dwi Santosa; Rizal Aditya Hidayat (Jurnal Transformasi Global, 2026)
This study analyzes the diplomatic strategy of Indonesia in mobilizing resources from the Bill & Melinda Gates Foundation (BMGF) for the national Tuberculosis (TB) vaccination agenda. TB is positioned as a complex Human Security threat, driven by market failure and inadequacies in Global Health Governance (GHG). Employing the Pluralism/Transnationalism perspective, this research examines how Indonesia, as a middle power, moved Beyond State-Centric during the 2010–2025 period. The findings indicate that Indonesian diplomacy was highly effective due to the implementation of a Co-governance Partnership strategy. This strategy leveraged sovereign assets (such as the roles of the BPOM and PT Bio Farma’s capacity) as bargaining power to institutionalize and steer BMGF's Philanthropic Soft Power. This effectiveness is measured by the successful mobilization of funding and technology transfer for the M72/AS01E TB vaccine clinical trials, significantly reinforcing national research and vaccine industry resilience. The core implication is the evidence that developing nations can assert their agency and sovereignty in negotiations with transnational actors, transforming traditional donor-recipient relationships into long-term capacity building investments. This study contributes to the IR literature by providing an analytical framework for middle powers to manage philanthropism in service of domestic Human Security interests.